Destroyer of Confidence: James Gordon Bennett, Jacksonian Paranoia, & the Original Confidence Man - Seybold, Matt (American Studies, 2018)
This essay resuscitates a critical discussion which began with Johannes Bergmann’s “The Original Confidence Man” for American Quarterly in 1969. Bergmann identified the first appearance of the term confidence man in print, in the New York Herald in 1849. Bergmann’s discovery of the American origins of the conman archetype initiated a series of investigations of its permutations in American Literature (see pg. 3 & note 4). What Bergmann and others failed to recognize, probably due to the limitations of newspaper archives in the 1960s and ‘70s, is how the conman archetype evolved within the wildly popular publication where it first appeared. James Gordon Bennett, the firebrand publisher of the Herald, invented the term (or, at least, appropriated it) for the express purpose of attaching it to his enemies. He found the epithet particularly suited to his ongoing vilification of Wall Street speculators and financiers. The conman, still a common trope in critiques of finance, has been intrinsically tied to the securities economy since his invention. In this essay, I trace the development of this connection in the Herald, arguing that Bennett uses it to invent a populist critique of speculation and securitization. He also identifies and debunks a “rhetoric of confidence” habitually employed by politicians, lobbyists, and bankers during economic crises. But the unintended consequences of Bennett’s active “destruction of confidence” are both a permanent change in the connotation of confidence and a promulgation of the paranoid style which prevents political compromise and provokes secession.